Cellular immune signatures and differences of four porcine circovirus type 2 vaccines to heterologous PCV2d infection - Shuai Li; Jiawei Liu; Lingbo Meng; Susu Yin; Hua Wu; Jianwen Zou; Dongbo Yuan; Hairong He; Guanghao Yin; Xianfeng Jia; Xiaoli Hao; Shaobin Shang (npj Vaccines)
Abstract Multiple PCV2 vaccines originating from different antigens and formula are commercially available and have shown great effectiveness in protecting pigs from clinical disease. However, our understanding of the immune mechanisms underlying these vaccine-induced protection is fairly limited, except for antibody responses. Head-to-head comparisons of T-cell responses induced by these vaccines in pigs would provide valuable insights into the mechanisms of protective immunity against PCV2. Here, T-cell responses in peripheral blood of pigs after vaccination with four representative PCV2 vaccines, as well as local and systemic recall responses following challenge with a PCV2d strain were examined. All four PCV2 vaccines induce a rapid cellular immune response that could be detected as early as 7 days post-vaccination. Some vaccine-primed CD4 T cells exhibit multifunctionality, being capable of secreting double (IFNγ/TNFα) and even triple cytokines (IFNγ/TNFα/IL-2) simultaneously. In contrast, a weak CD8 T cell response was also detected in the vaccinated pigs but just IFNγ/TNFα double producer and lack of cytotoxicity. These vaccine-activated CD4 and CD8 T cells displayed phenotypes of effector memory or terminally-differentiated effector memory T cells, which rapidly expand to subsequent PCV2d challenges. Prior-vaccinated pigs exhibited a stronger T cell cytokine response post-challenge, being most evident in the spleen. Notably, the cellular immune response induced by different types of PCV2 vaccines exhibited high similarity in phenotypic and functional properties, while showing significant differences in kinetics and magnitude. These results advance our understanding of cell-mediated immune protection afforded by different PCV2 vaccines and unravel fundamental differences in cellular immune response induced by PCV2 vaccines utilizing diverse technologies.